2011
DOI: 10.1038/jcbfm.2011.130
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical Capillary Flow Pulsatility is Not Elevated in Experimental Communicating Hydrocephalus

Abstract: While communicating hydrocephalus (CH) is often characterized by increased pulsatile flow of cerebrospinal fluid (CSF) in the cerebral aqueduct, a clear-cut explanation for this phenomenon is lacking. Increased pulsatility of the entire cerebral vasculature including the cortical capillaries has been suggested as a causative mechanism. To test this theory, we used two-photon microscopy to measure flow pulsatility in neocortical capillaries 40 to 500 lm below the pial surface in adult rats with CH at 5 to 7 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
3
7
0
Order By: Relevance
“…The speed of that fluid pulse wave is influenced by the shear modulus and the distensibility of vascular walls and, within the brain, can vary from 0.4 m/s (in proximal segments of the middle cerebral artery 35 ) down to very small values of 0.3 mm/s in the neocortical capillaries of the mouse brain. 36 Passage of the fluid pulse wave during CAP systole is associated with a transient increase in the fluid fraction, which could explain the observed systolic brain softening and increased viscosity in our study. Furthermore, the observed disseminated effect could be explained by the fluid pulse wave speed within perforating arteries in WM, which is 0.5–1.0 cm/s 35 and is still too fast for a spatially resolved analysis in ssMRE.…”
Section: Discussionsupporting
confidence: 50%
“…The speed of that fluid pulse wave is influenced by the shear modulus and the distensibility of vascular walls and, within the brain, can vary from 0.4 m/s (in proximal segments of the middle cerebral artery 35 ) down to very small values of 0.3 mm/s in the neocortical capillaries of the mouse brain. 36 Passage of the fluid pulse wave during CAP systole is associated with a transient increase in the fluid fraction, which could explain the observed systolic brain softening and increased viscosity in our study. Furthermore, the observed disseminated effect could be explained by the fluid pulse wave speed within perforating arteries in WM, which is 0.5–1.0 cm/s 35 and is still too fast for a spatially resolved analysis in ssMRE.…”
Section: Discussionsupporting
confidence: 50%
“…But when we controlled for age, we did not find any significant correlations between hypertension and the CSF variables, suggesting that the two phenomena are not linked. As such, our finding supports Rashid et al 43 who found in a rat study that elevated pulsatile CSF flow in the aqueduct was not matched by an increase in microvascular pulsatile flow. Furthermore, our regression analysis model indicated that both hypertension and NPF were significant predictors of DAWM formation, suggesting that the two mechanisms may be acting independently of each other to produce WM SA changes.…”
Section: Discussionsupporting
confidence: 93%
“…This could relate to the fact that surface capillary pulsatility in hydrocephalic brains is not substantially altered. 45 We should note that other investigators have used "preconditioning" as a means of obtaining more consistent data during mechanical testing in live brain, eg, several indentations are applied before the ultimate test data are acquired. 46 The basic premise is that preconditioning redistributes the tissue fluid to produce a more consistent response and a smaller intersample variability.…”
Section: Discussionmentioning
confidence: 99%